Answer:
x=10
y=-3
Step-by-step explanation:
3x + 5y= 15...eqn. 1
2x + 4y= 8...eqn. 2
multiply eqn. 1 by 2 and eqn. 2 by 3
6x + 10y = 30...eqn. 3
<u>6x</u><u> </u><u>+</u><u> </u><u>12y</u><u> </u><u>=</u><u> </u><u>24...eqn. 4</u>
0 - 2y = 6
divide both sides by the coefficient of y which is -2
<u>- 2y</u> = <u>6</u>
- 2 -2
y= -3
Put y= -3 into eqn. 1
3x + 5(-3) = 15
3x - 15 = 15
3x =15 + 15
<u>3x</u> =<u> 30</u>
3 3
x = 10
Therefore X= 10 and Y= -3
Answer:
The correct answer for the second one is,
![- 36 {a}^{5} {b}^{5} {c}^{2}](https://tex.z-dn.net/?f=%20-%2036%20%7Ba%7D%5E%7B5%7D%20%20%7Bb%7D%5E%7B5%7D%20%20%20%7Bc%7D%5E%7B2%7D%20)
Solve for c by simplifying both sides of the equation, then isolating the variable.
C=36.5
Answer: 18%
Step-by-step explanation: Add 36 + 14 = 50
Then 36*50/100=18
Answer:
13) Is a linear function. The points form a straight line
14) Is an exponential function. The points form a curved line.